Nutritional Transformation of Ruminant Feed: A Literature Review on the Role of Fermentation in Enhancing Productivity - Hajar Hajar (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2025)
Feed is a fundamental component in ruminant livestock production systems, directly influencing productivity and overall efficiency. Given the limited availability of high-quality feed resources, feed fermentation emerges as a promising strategy to enhance the nutritional value of abundant and low-cost local feed materials. The fermentation process involves the activity of microorganisms capable of hydrolyzing anti-nutritional compounds, improving fiber digestibility, enriching protein content, and generating beneficial secondary metabolites that support digestive health. This literature review aims to examine existing research on feed fermentation mechanisms, types of microorganisms employed, changes in nutrient composition, and the effects on ruminant performance, including feed intake, feed conversion efficiency, weight gain, and milk production. The findings indicate that fermentation using lactic acid bacteria, fungi, or yeast significantly improves the quality of fibrous feeds such as rice straw, cassava leaves, and agro-industrial by-products. Consequently, animal performance improves, accompanied by enhanced feed efficiency. Therefore, feed fermentation technology holds substantial potential in supporting sustainable livestock systems, particularly in areas with limited access to high-quality feed. This review highlights the need for standardization of fermentation techniques and comprehensive economic evaluations to facilitate large-scale adoption.